Strategy for Improving Public Services Based on Balanced Scorecard in the Department of Transportation of West Bandung District - Zairusi, Zairusi; Muis, Abdul (Jurnal Manajemen Pelayanan Publik, 2025)
This study aims to analyze the implementation of Balanced Scorecard in the West Bandung Regency Transportation Agency as a strategic tool to measure and manage organizational performance in the public sector. Amid challenges in ensuring accountability and service quality, this research addresses the problem of performance inefficiency in public transportation services. The research method used is qualitative with a case study approach, which utilizes secondary data from performance reports, policy documents, and public satisfaction surveys. Through the analysis of four main perspectives of balanced scorecard —finance, customer, internal process, and learning and growth—this study shows that the implementation of balanced scorecard can improve the efficiency and effectiveness of public services. From a financial perspective, Dishub KBB can optimize budget management and resource allocation to support transportation infrastructure and public transportation subsidies. The customer perspective highlights the importance of measuring public satisfaction related to punctuality, safety, and service quality. Efficiency in internal processes allows for the identification and improvement of operational bottlenecks. Finally, learning and growth show that innovation and human resource development are key to facing challenges and improving service quality. This study makes a significant contribution to the development of performance management models in the public sector.